REGENERATION IN PINE STANDS AFTER THE FIRST CONVERSION FELLING - Zhezhkun, A. N.; Porohnyach, I. V. (Forestry and Forest Melioration, 2018)
During conversion felling of middle-aged and ripening pine stands in fresh fairly infertile pine-oak forest type, the best conditions for the pine regeneration are formed in the satisfactory seed production years, on the rounded gaps with a diameter of one average height of the stand, formed as a result of first felling. The most effective procedure to promote natural regeneration is plowed furrow tillage. Under satisfactory pine regeneration, the next felling can be performed in 4–5 years. In nonseed year, implementation of the first felling is not effective for natural pine regeneration. Next year, under sufficient seed production, regeneration is deteriorated due to turf formation, which increases the regeneration period and the interval between the attempts of conversion felling.